PERTUMBUHAN KOMPENSASI PADA IKAN NILA MERAH (Oreochromis niloticus) DENGAN INTERVAL WAKTU PEMUASAAN YANG BERBEDA - Cahyono Purbomartono; Hartoyo Hartoyo; Agus Kurniawan (Universitas Gadjah Mada, 2009)
In aquaculture, efficiency of feed is very important to decrease cost production. Besides, excess of feed consumptions caused disturbance of water quality which affected on productivity and survival rate. Fasting day interval was one of best chosen method to make efficiency and effectively on feeding schedule. The research was aimed to know the effect on fasting day interval against its growth and survival rate. Experimental design used was completely randomized design with 4 treatments, 3 replication. The treatments were: P1 (1 day given feed, 1 day fasted), P2 (2 day given feed, 1 day fasted), P3 (3 day given feed, 1 day fasted), P4 (given feed everyday/control). Red nile used gave length 7–10 cm and weight 10 - 19 g were placed on cement pond 1 m2 of sized. Fish density was 20 fishes/m2 with fed consumption about 3% daily of total biomass weight. Result showed that treatment using fasting day interval on red nile fish did not affect on both compensatory growth and its survival rate. Better growth occurred at P4 which fed intake consumption everyday without fasted. While P1 revealed same result (p>0,05) on survival rate with P4.